Analysis of strengthened short deficient rubberized concrete-filled steel tubular columns (Fracture and Structural Integrity, 2020)
Concrete-filled steel tubular (CFST) columns are broadly used in many structural systems for their well-known merits. This paper presents a finite element investigation on the structural behaviour of short circular deficient steel tubes filled with rubberized concrete (RuC), under axial compressive load. To accomplish this study, a validation of the proposed three-dimensional nonlinear finite element model; using ANSYS software; was carried out showing good accurateness. The analysis involved two different concrete mixes with 5% and 15% replacement of fine aggregate volume with crumb rubber particles. Columns strength reduction due to horizontal or vertical deficiencies was handled by increasing the thickness of the steel tube or wrapping the columns with two different types of FRP sheets. Five strengthening arrangements were studied using GFRP sheets and CFRP sheets. The results indicated that the ultimate bearing capacity of the RuCFST columns was increased with increasing the steel tube thickness. application of FRP sheets for strengthening the deficient RuCFST columns efficiently managed to retrieve the strength-lost due to either horizontal or vertical deficiency. Moreover, an enhancement in the columns’ ductility was observed especially when using GFRP sheets
Keywords: Rubberized concrete; Axial compression; Deficiencies; RuCFST; FRP